CONCEPTUAL FOUNDATIONS OF THE NATIONAL BUSINESS RECOVERY STRATEGY IN UKRAINE - Tkachenko, Volodymyr; Molchaniuk, Anzhela; Leonova, Yelyzaveta (Social Development: Economic and Legal Issues, 2026)
The article examines the theoretical and applied foundations of formulating a national business recovery strategy in Ukraine under conditions of war economy and post-war reconstruction. The relevance of the research is driven by the unprecedented scale of damage inflicted on the national economy by full-scale hostilities, with documented direct losses to Ukraine’s infrastructure exceeding 143.8 billion in the first year of war alone, which requires not merely sectoral recovery but a comprehensive structural transformation of the economic system. International experience in implementing recovery strategies is analyzed, in particular that of the Republic of Korea, which demonstrated the effectiveness of comprehensive enterprise restructuring programs combined with large-scale technological modernization investments after the 1997–1998 Asian financial crisis, and Israel, whose YOZMA system illustrates a viable model for supporting technological entrepreneurship under permanent security threats through state-venture investment and tight cooperation between the defense-industrial complex and the civilian sector. The necessity of a comprehensive approach to strategy development is substantiated, taking into account sectoral specifics, the regional dimension, and institutional preconditions. A conceptual model of the national recovery strategy with a 7–10-year implementation horizon is proposed, and its priority areas are defined: reintegration of small and medium-sized enterprises, digital transformation of business, attraction of foreign direct investment, and implementation of public-private partnerships. A three-level institutional architecture for strategy management is developed, comprising strategic, operational, and implementation levels with clearly defined competencies between the Interagency Recovery Council, the Recovery Agency of Ukraine, and its regional offices. A monitoring system based on evidence-based policy principles is proposed, including input, process, and outcome evaluation supplemented by key performance indicators such as GDP and gross value-added growth rates, the dynamics of operating enterprises, attracted FDI volumes, and the Purchasing Managers’ Index. It is established that effective recovery requires the synchronization of state support measures, reform of the regulatory environment, and the stimulation of innovative activity of enterprises.